2018
DOI: 10.1159/000487324
|View full text |Cite
|
Sign up to set email alerts
|

Early and One-Year Outcomes of Acute Stroke in the Industrial Region of Poland During the Decade 2006–2015: The Silesian Stroke Registry

Abstract: Background: Poland, classified as a high-income country, is still considered to have a high cardiovascular risk population. During the last decade, the standards of care in acute stroke (AS) had markedly improved; thus, we aimed to assess whether and how it translated into early and late outcomes. Methods: Silesian Stroke Registry was created from the administrative database of the public, obligatory, health ­insurer in Poland. The AS cases were selected based on primary diagnosis coded in ICD-10 as I60-I64 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
1
12
1
1
Order By: Relevance
“…The in-hospital mortality in patients either with RIS or FIS was significantly higher in cardiogenic stroke compared to atherogenic stroke (Tab. [14][15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-hospital mortality in patients either with RIS or FIS was significantly higher in cardiogenic stroke compared to atherogenic stroke (Tab. [14][15].…”
Section: Resultsmentioning
confidence: 99%
“…The first epidemiological data on cerebrovascular diseases in Poland comes from the years 1980-2010 [1][2][3][4][5][6][7][8][9][10][11][12][13]. The most recent studies, both national and regional, were conducted in the last decade [14][15][16][17]. Some of them have concerned the Silesian Province, an industrial region of Poland covering 12% of the nation's population (4.6 million people).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the standard of stroke care in Poland has markedly improved, mainly due to the development of a network of stroke units. Most recent studies, both national and regional, have reported decreasing early and late fatality rates as well as lower admission rates, not only for first-ever but also recurrent strokes [14,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Однако реальная клиническая практика лишь в малой степени соответствует тому, что сформулировано в клинических рекомендациях [10][11][12][13][14][15].…”
Section: Outpatient Registry Of Stroke Region амбулаторный регистр моunclassified